THE INFLUENCE OF PRICE AND TRUST ON CONSUMER SATISFACTION IN SHOPPING ONLINE SHOP (TOKOPEDIA) IN SAMPIT - Hari Susanto; Muamar Muamar; Deky Prasetyo; Eko Cahyo Purnomo; Andri Riyadi (SEAN Institute, 2023)
This study is entitled the effect of price and trust on consumer satisfaction in shopping online shop (Tokopedia) in Sampit. This study uses a random sampling method. The population in this study was 100 and the sample used was 80 people who were consumers in Sampit, and the data was tested using validity test, reliability test, hypothesis testing and research data analysis using descriptive analysis, multiple linear regression analysis, correlation coefficient analysis and determination analysis. The results showed that the correlation coefficient value (r) was 0.792, the R Square value (r2) was 0.627, which was included in the Strong correlation position with the standard (0.60 - 0.799), meaning that Price and Trust together have a positive and strong relationship to Customer Satisfaction, stating that the two independent variables, namely Price (X1) and Trust (X2) affect the dependent variable, namely Customer Satisfaction (Y) by 62.7% and the remaining 37.3%. Based on the results of multiple linear regression tests, the equation Y = 2.323 + 0.372 + 0.478 is obtained, which shows that there is a positive relationship between the independent variables and the dependent variable.